The high overtone and combination levels of SF6 revisited at Doppler-limited resolution: A global effective rovibrational model for highly excited vibrational states. (March 2017) - Faye, M.; Boudon, V.; Loëte, M.; Roy, P.; Manceron, L.
Abstract: Sulfur hexafluoride is an important prototypal molecule for modeling highly excited vibrational energy flow and multi quanta absorption processes in hexafluoride molecules of technological importance. It is also a strong greenhouse gas of anthropogenic origin. This heavy species, however, features many hot bands at room temperature (at which only 30% of the molecules lie in the ground vibrational state), especially those originating from the lowest, v6 =1 vibrational state. Using a cryogenic long path cell with variable optical path length and temperatures regulated between 120 and 163 K, coupled to Synchrotron Radiation and a high resolution interferometer, Doppler-limited spectra of the 2 ν 1 + ν 3, ν 1 + ν 2 + ν 3, ν 1 + ν 3, ν 2 + ν 3, 3 ν 3, ν 2 + 3 ν 3 and ν 1 + 3 ν 3 from 2000 to 4000 cm-1 near-infrared region has been recorded. Low temperature was used to limit the presence of hot bands. The spectrum has been analyzed thanks to the XTDS software package. Combining with previously observed weak difference bands in the far infrared region involving the v1, v2, v3 =1 states, we are thus able to use the tensorial model to build a global fit of spectroscopic parameters for v1 =1, 2, v2 =1, v3 =1, 2, 3. The model constitutes a consistent set of molecular parameters and enable spectral rovibrational simulation for all multi-quanta transitions involving v1, v2 and v3 up to v 1 − 3 = 3 . Tests simulation on rovibrational transitions not yet rovibrationally assigned are presented and compared to new experimental data. Abstract : Highlights: High resolution study of fundamental, combination and overtone bands of SF6 . Simultaneous fit of eleven bands data including v1, v2, and v3 modes. Prediction four quanta transitions.